Effect of amino acids on sperm motility, velocity parameters, plasma membrane integrity and lipid peroxidation levels at cooled and post–thawed ram epididymal semen - SANGEETA, SHARON; KULKARNI, S; ARANGASAMY, A; SELVARAJU, S (The Indian Journal of Animal Sciences, 2015)
This study is focused to look into the possibility of including amino acids during cryopreservation to improve the quality of frozen semen in sheep. Cauda epididymal semen was collected from 2-3 year-old Bannur crossbred rams slaughtered at the local abattoir. The semen samples were diluted in tris egg yolk glycerol diluent along with different additives and made into 7 aliquots. Aliquot 1 served as control, L-alanine was added @ 100 and 135mM in the aliquot 2 and 3, L-glutamine was added @ 20 and 25mM in the aliquot 4 and 5 and L-proline was added @25 and 50mM in the aliquot 6 and 7, respectively. Diluted semen was filled in 0.25 ml French straws, sealed manually and equilibrated at 4oC for 2 h, cooled in LN2 vapour before being plunged into LN2 till further evaluation. Inclusion of L-proline and L-glutamine in the diluent significantly increased the percent live sperm, total motility, lipid peroxidation and maintained higher functional membrane and acrosomal integrity than the control group. In contrast, L-alanine decreased the percentage of total motility, fast progressive spermatozoa and increased the percentage of immotile spermatozoa. It can be concluded that 20mM L-glutamine and 25mM L-proline can be used as semen additive to freeze ram epididymal semen as they prevented cryo injuries to sperm and improved the pre-freeze and post-thaw semen characteristics.